Conversor boost quadrático pwm associado à célula de auxílio à comutação SR-ZVS-QRC - Vilefort, Leandro Sousa (2011)
This work presents a Quadratic Boost PWM converter associated to the auxiliary commutation cell SR-ZVS-QRC. The proposed converter has high voltage gain, low switching losses and reduced electromagnetic interference (EMI), making it suitable for fuel cells (H2) applications. There will be presented operation steps, main waveforms, phase diagram, static gain equation, graphics of static gain by duty cycle (D) for different operating points and experimental results of implemented prototype assembled in the laboratory.